Market Entry and Competition Under Network Effects - Feng, Yinbo; Hu, Ming (Operations Research, 2024)
The “long tail” theory was celebrated by BusinessWeek as the biggest idea of the year 2004, soon after the book The Long Tail by Chris Anderson was published. The long tail theory calls for applying a low-budget strategy—producing a (relatively) large number of products with (relatively) low investment levels. However, some other cultural industries may tell a different story. The concentration of the most popular titles in the video game industry is growing, a phenomenon known as the blockbuster phenomenon. This phenomenon suggests that firms may adopt a high-budget strategy—producing a (relatively) small number of products with (relatively) high investment levels. In “Market Entry and Competition Under Network Effects,” Y. Feng and M. Hu analytically study the impact of a network effect on entry decisions and investment strategies (i.e., the high-budget versus low-budget strategies) adopted by competing firms based on which they further provide a theory that links the ex post sales volume concentration with the ex ante product variety in a market under network effects.